Impact of Organizational Characteristics, CEO Education, and Firm Ownership on the Adoption and Effectiveness of High Performance Work System in Vietnam - Phuong, Tran Huy (Organizations and Markets in Emerging Economies, 2020)
In spite of tremendous research on the relationship between HPWS and firm performance, a paucity of them has examined the antecedent of HPWS. Data were collected from CEOs and HRM managers from 311 firms including state-owned, private and foreign invested enterprises. Multiple regression analysis suggests that (1) firm characteristics (firm capital, firm age) and CEO’s education were positively associated with the adoption of Ability-Motivation-Opportunity bundles of HPWS, (2) HPWS were positively associated with firm performance, and (3) ownership style moderates the relationship between HPWS and firm performance in different manners. Theoretical and practical implications were discussed.
Keywords: high performance work system; organizational characteristics; firm ownership; adoption; Vietnam